2005
DOI: 10.1002/ppul.20185
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced respiratory symptoms are poor predictors of bronchoconstriction

Abstract: Exercise-induced asthma (EIA) is a possible cause of poor physical performance in children. No data are available on the value of respiratory symptoms to discriminate children with bad physical fitness from children with EIA. We evaluated respiratory symptoms in school-age children during and after exercise in relation to EIA. The population of 149 primary schools (849 classes with 15,241 children) was enrolled in the study. EIB was assessed using the 6-min free-running-test (6MFRT) in 15,241 children. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 20 publications
3
65
1
1
Order By: Relevance
“…The first visit consisted of an interview about asthma, medication, measurements of height, weight, fractional exhaled nitric oxide (FeNO) and venous blood samples for analyses of Immunoglobulin E (IgE) sensitization and eosinophil cationic protein (ECP). The second visit (at an average of 12 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) days later (median (interquartile range)) consisted of a standardized exercise challenge test on a treadmill with dry-air inhalation to detect EIB. 5 Ethical approval was obtained from the ethics review board in Uppsala, Sweden (Dnr 2011/413).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first visit consisted of an interview about asthma, medication, measurements of height, weight, fractional exhaled nitric oxide (FeNO) and venous blood samples for analyses of Immunoglobulin E (IgE) sensitization and eosinophil cationic protein (ECP). The second visit (at an average of 12 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) days later (median (interquartile range)) consisted of a standardized exercise challenge test on a treadmill with dry-air inhalation to detect EIB. 5 Ethical approval was obtained from the ethics review board in Uppsala, Sweden (Dnr 2011/413).…”
Section: Methodsmentioning
confidence: 99%
“…4 In subjects without asthma, a prevalence of 10 to 20% was reported. [4][5][6] Some studies have reported a higher prevalence in girls than in boys, 7,8 while others have not revealed any gender differences. 9,10 Exercise test is recommended to confirm EIB as exercise-induced symptoms have poor predictive value for EIB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, exercise-induced cough has been shown to be a poor predictor of bronchoconstriction. (32) Nonetheless, considering asthma as a diagnosis in the absence of wheeze is not unjustified. If the child is not wheezing during consultation, accurate identification of wheeze from history-taking alone can be difficult.…”
Section: Coughmentioning
confidence: 99%
“…Field studies in unselected primary school children have described the distribution of lung function changes after exercise (3,4) or tested prevalence of exercise induced bronchoconstriction (EIB) in relation with respiratory symptoms (5,6). In these studies, the response was expressed as largest fall in forced expiratory volume in 1 s (FEV1) within 10 -15 min of exercise cessation (3,4) or considered positive when peak expiratory flow decreased 15% or more (5,6). To the best of our knowledge, whether significant change in airway caliber occurs in healthy children during the recovery from exercise has not been documented.…”
mentioning
confidence: 99%